Mechanical properties and microstructure of recycled mortar reinforced with hybrid fiber - Ismail, Sallehan; Asri Abd Hamid, Mohammad; Yaacob, Zaiton; Ismail, Dzulkarnaen; Md Akil, Hazizan (International Journal of Engineering and Technology, 2018)
This study investigated the hybrid effects of two types of microfiber, namely, polypropylene and nylon, on the mechanical properties of high-strength mortar, which produced fine recycled aggregate (FRA). The amount of microfibers was maintained at a volumetric fraction of 0.6%. The microstructure and mechanical strength properties (compressive strength and flexural strength) of recycled mortar reinforced with hybrid-size microfibers were evaluated at various curing ages. Experimental results show that the inclusion of hybrid fibers significantly influenced the mechanical performance of the recycled mortar. The hybridization fiber at volume fraction 0.3% polypropylene + 0.3% nylon yielded the most promising mechanical performance. Enhancements of 8% on compressive and 11% flexural strength were achieved at 28 days. Scanning electron microscopy observations revealed that reinforcement at the microscale prohibited the initiation and growth of cracks at the micro level. High loads were required to form macrocracks within composites, thereby improving the mechanical strength of the mortar matrix.Â Â